The Position of Licensed Industries With Special Emphasis of The Republic of Macedonia - Marko Andonov; Kristina Misheva; Zoran Mihajloski (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
Regulation of professions that provide services to the public is necessary to ensure the quality of their services and to protect the interests of their users. However, it can have adverse effects like eliminating or restricting the competition and reducing the transparency. Therefore, establishing a balance between the interest that is supposed to be achieved by regulation and the need to allow competition is becoming more obvious. This is particularly evident when applying regulatory standards in small economies. While the main principles of competition and regulation as developed in major economies are suitable for small economies, the application should be different due to the characteristics of the small and limited markets. The paper will cover three professions - lawyers, accountants and architects as the most numerous and longest present on the Macedonian market. With the review of the regulation of these professions, a comparison with the regulation of these professions in other countries will be done. The purpose of the paper is based on the comparison and the experience in the operation of the regulated professions and industries in Macedonia, to make recommendations for the establishing regulatory systems that will enable protection of public interests and development of these industries.
Keywords: 650; Regulation; Profession; Licensed industries